ANALISIS MATERIAL ALUMINIUM ALLOY TERHADAP LAJU KOROSI YANG DI SEBABKAN OLEH UDARA LAUT PADA STRUKTUR LEADING EDGE PESAWAT - Muhammad Nur Abid Fakhri Fakhri; Heru Susanto; Muhammad Luqman Bukhori (Sekolah Tinggi Teknologi Kedirgantaraan, 2022)
Corrosion is a property of a material that causes the material to lose its weight and strength where this corrosion property factor can occur because it is caused by environmental conditions that result in the effect of corrosion on the material. In the world of aviation, corrosion is a matter of great concern to aircraft technicians because if you ignore this corrosion, it will greatly disrupt the activities of the aircraft. And on the plane most use aluminum alloy material, especially on the leading edge the material is made of aluminum alloy. To find out the corrosion that occurs on the aircraft, we can do material testing such as micro photo testing and weight loss in order to see how fast the corrosion rate is on the aluminum material. Therefore, in order to slow down the corrosion rate on the aluminum alloy material, a coating using a mixed inhibitor layer, namely potassium chromate and sodium chromate, will be carried out to slow down the corrosion rate that occurs.